Ukraine 2019 Public Expenditure and Financial Accountability Performance Assessment Report - World Bank (World Bank, Washington, DC, 2020)
The main purpose of the 2019 PEFA assessment is to provide the Government of Ukraine with an objective and up-to-date diagnostic of the national-level public financial management performance based on the latest internationally recognized PEFA methodology. The 2019 PEFA is an assessment of the quality of the Ukrainian PFM system and monitors the results achieved through PFM reforms undertaken since the 2015 PEFA assessment. More specifically, the PEFA assessment measures which processes and institutions contribute to the achievement of desirable budget outcomes, aggregate fiscal discipline, strategic allocation of resources, and efficient service. The assessment covers the central government. It also includes the Ministry of Economy as the authorized body for Procurement Service, State Audit Service, Budget Committee of the Verkhovna Rada of Ukraine (Parliament), State Fiscal Service of Ukraine (revenue administration), and Accounting Chamber of Ukraine (supreme audit body). It also assesses aspects of the three extra-budgetary funds and qualifying state-owned enterprises in terms of the relevant indicators. A substantial number of government officials participated in the assessment.